Identification and culture of proliferative cells in abnormal taenia solium larvae: Role in the development of racemose neurocysticercosis - Orrego, Miguel A. (2021)
This work was supported by National Council for Science, Technology, and Technological Innovation (CONCYTEC) – World Bank, through its executing unit National Fund for the Development of Science, Technology, and Technological Innovation (FONDECYT) contract [E033-01-08-2018-FONDECYT/Banco Mundial Programas de Doctorado en A´reas Estrate´gicas y Generales], Fogarty International Center-National Institutes of Health Training grant D43 TW001140, and by Intramural National Institutes of Allergy and Infectious Diseases (NIAID), National Institutes of Health. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.